2020
DOI: 10.11113/jt.v82.14185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Flow Obstruction in a Condensing Unit on Split Air Conditioner Performance

Abstract: Obstructions of air flow in the outdoor unit could block the condenser air flow and reduce its heat rejection As a result, it could decrease the performance of a room air conditioning system. The paper presents the effects of the air flow obstruction of a condensing unit on the performance of a split-type air conditioner with refrigerant R410A. The study was conducted experimentally by employing front and side obstructions with varied distance from the condensing unit. The front obstruction of 100 cm height wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As a comparison, it was reported that obstruction of the air flow in the front and side of condenser gives an increase of power consumption by 2.4% for each 1℃ of increase of condensing temperature [6]. Kumbhar et al [20], whereas, informed that each 1℃ increase of condensing temperature gives an increase of input power by 1.7% based on their experiment using water chiller.…”
Section: Power Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a comparison, it was reported that obstruction of the air flow in the front and side of condenser gives an increase of power consumption by 2.4% for each 1℃ of increase of condensing temperature [6]. Kumbhar et al [20], whereas, informed that each 1℃ increase of condensing temperature gives an increase of input power by 1.7% based on their experiment using water chiller.…”
Section: Power Consumptionmentioning
confidence: 99%
“…The mass flow rate of the supply air can be expressed by using the multiplication of air flow rate (Q) and air density (), or ṁ=Qρ (6) In Eq. ( 6), the volumetric flow rate is expressed in m 3 /s while the air density is expressed in kg/m 3 .…”
Section: Calculation Of Cooling Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of condensing temperature could also be caused by the reduction of air flow in the condenser caused by air blockage. An increase of energy consumption by 36% and decrease of cooling capacity by 46% were reported when an obstacle is installed in the front of condenser at a distance of 10 cm [9]. The effect of the obstacle decreases with the increase of the distance between the condenser and the obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…This study also noted that the power consumption increased by 10.2%, while the capacity and energy efficiency reduced by 7.9% and 16.5%, respectively. Similar to the high outdoor air DBT, the presence of condenser obstruction decreases the capacity and COP of an air conditioner [26]. The effect has been experimentally investigated by installing airflow barriers in front and side of condenser.…”
Section: Introductionmentioning
confidence: 99%